Linear Programming approach in fruits production in Johor - Teh, Ching Yee; Mohd Razali, Siti Noor Asyikin binti (Enhanced Knowledge in Sciences and Technology, 2022)
Linear Programming is an optimization method mostly use in resource allocation and achieving efficiency in production planning particularly in achieving increased agriculture production of fruits. However, the supply of fruits is not enough and to adjust the wages of workers in agriculture. This study carried out to maximize the productivity of the fruits and minimize the wages of workers. Two data set were collected through DOSM due to covid-19 pandemic. The first data set such as types of fruits, area planted and value production while second data set such as number of workers and labor productivity were collected. The problem was solved using Linear Programming method and the proposed solution obtained using Excel Solver and Tora software. The sensitivity analysis was also performed in this study. The result showed that the four types of fruits should put more focus on and cut down the numbers of workers but increase a little bit on salary to reach optimal result. This could helped the agriculture sector reached maximum profit between RM3364164.35 and RM3364221.11 annually and hired workers with optimum salary with RM1865.85. For future study, it was recommended to obtain data from related authorities and investigated in other fields.